Crime in Creole countries: a sketch of criminal ethnography - Corre, Armand (Lexington Books, 2021)
"This book provides an unvarnished account and contemporaneous interpretation of criminal activities at a time in which the French colonies within the West Indies were transitioning from slavery to emancipation. The firsthand account depicts the inhumanity of this historical time-frame"--